Analisis Bibliometrik: Kreativitas Anak Dalam Keterampilan Menggambar Pembelajaran Seni Rupa - Jaka pertandang, Mohamad Afif; Julia, J.; Nugraha, Dadan (Jurnal Pena Ilmiah, 2021)
This study aims to analyze various journal articles obtained through Scopus using Publish or Perish in the period 2010-2021, and the research topic is drawing skills. The research studies include: publication trends, most used keywords, most used titles, most used abstracts, and author collaboration. The research method used is bibliometric analysis. The data obtained were 89 in the period 2010-2021, then the data was selected through Microsoft Excel and obtained 61 data. The results of the study show that the highest publication trend occurs in 2019 and 2021, while the lowest publication trend occurs in 2013. The most widely used keyword is drawing with 10 links. The most used titles are skills with 46 linkages. The most widely used abstracts are skills with 115 links and 48 events. Author collaborations that contributed the most were Setiawan, A.H., Trianingsih, L., and Takaoka, R.